2008
DOI: 10.1007/s10725-008-9303-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous abscisic acid (ABA) on cucumber seedling leaf carbohydrate metabolism under low temperature

Abstract: Seedlings with four true leaves of cucumbers (Cucumis sativus L.), Guonong No.25 (a coldtolerant cultivar) and Guonong No.41 (a cold sensitive cultivar), were grown under normal or low temperature conditions: 25°C/18°C or 15°C/8°C (day/night). The seedlings of Guonong No.25 under low temperature were also treated with or without exogenous ABA. The purpose of our study was to find out the effects of low temperature and exogenous ABA application on the carbohydrate metabolism in the cucumber plants. Time course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…We detected 260 genes with repeatable cold-tolerance QTLs (reCT-QTLGs) and 301 genes with repeatable quality and yield QTLs (reQY-QTLGs) in these pathways (Tables S9 and S10). Phytohormones play important roles in the adjustment to adapt to the environmental stresses222829. Consistent with these findings, ABA biosynthesis reCT-QTLG ( nine-cis-epoxycarotenoid dioxygenase 3, NCED3 ), jasmonate biosynthesis reCT-QTLG ( OPDA reductase 3, OPR3 ) and ethylene biosynthesis reCT-QTLGs (1-aminocyclopropane-1-carboxylate synthase 7 and ethylene signal DNA binding/transcription factor) were detected in the hormone synthesis and metabolism pathway (Fig.…”
Section: Resultssupporting
confidence: 81%
“…We detected 260 genes with repeatable cold-tolerance QTLs (reCT-QTLGs) and 301 genes with repeatable quality and yield QTLs (reQY-QTLGs) in these pathways (Tables S9 and S10). Phytohormones play important roles in the adjustment to adapt to the environmental stresses222829. Consistent with these findings, ABA biosynthesis reCT-QTLG ( nine-cis-epoxycarotenoid dioxygenase 3, NCED3 ), jasmonate biosynthesis reCT-QTLG ( OPDA reductase 3, OPR3 ) and ethylene biosynthesis reCT-QTLGs (1-aminocyclopropane-1-carboxylate synthase 7 and ethylene signal DNA binding/transcription factor) were detected in the hormone synthesis and metabolism pathway (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Low temperature is one of the major environmental factors impacting plant growth, development and ecological distribution (Allen and Ort, 2001). A variety of crops from tropical and sub-tropical regions, such as maize, tomato, cucumber, and mango, are sensitive to cold when cultivated in temperate environments (Jones and Ort, 1998; Allen and Ort, 2001; Meng et al, 2008). As people have begun introducing plants from warm climates into cool climates, it has become important to understand the effects of LNT stress, which needs substantially more research.…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid (ABA) and indole-3-acetic acid (IAA) are involved in the development of defence responses during adaptation to drought (Pustovoitova et al 2004). In our laboratory, we found that exogenous ABA could improve tolerance to low temperature (Meng et al 2008); pre-treatment of seeds with ABA is much easier than spraying ABA on seedlings. Unfortunately, no detailed study has been conducted to describe how seedlings grown from ABA pre-treated cucumber seeds are affected.…”
Section: Introductionmentioning
confidence: 99%